Reticular fibre structure in the differential diagnosis of parathyroid neoplasms - Xiumei Hu; Shurong He; Xingran Jiang; Ping Wei; Xiang Zhou; Zhongyue Shi; Xue Li; Jun Lu; Hongying Zhao; Bojun Wei; Mulan Jin (BMC, 2023)
Abstract Background To investigate the characteristics of reticular fibre structure (RFS) in parathyroid adenoma (PTA), atypical parathyroid tumour (APT), and parathyroid carcinoma (PTC), and to assess its value as a diagnostic indicator. Methods Clinical data and pathological specimens of patients with PTA, APT or PTC were collected. Reticular fibre staining was performed to observe the characteristics of RFS. This study evaluated the incidence of RFS destruction in parathyroid tumours, compared RFS destruction between primary PTC and recurrent and metastatic PTC, and explored the association between RFS destruction and clinicopathological features of APT and primary PTC. Results Reticular fibre staining was performed in 50 patients with PTA, 25 patients with APT, and 36 patients with PTC. In PTA cases, a delicate RFS was observed. In both the APT and PTC groups, incomplete RFS areas were observed. The incidence of RFS destruction was different among the PTA, APT, and PTC groups (P < 0.001, χ2-test), at 0% (0/50), 44% (11/25), and 86% (31/36), respectively. When differentiating PTC from APT, the sensitivity and specificity of RFS destruction were 81% and 56%, respectively. The incidence of RFS destruction was 73% (8/11) in the primary PTC group and 92% (23/25) in the recurrent and metastatic PTC groups. In both the APT group and primary PTC group, no correlation was found between RFS destruction and clinicopathological features. Conclusion RFS destruction may indicate that parathyroid tumours have unfavourable biological behaviours.Reticular fibre staining may be a valuable tool for improving the diagnostic accuracy in parathyroid tumours.